2011
DOI: 10.1039/c0ob01102a
|View full text |Cite
|
Sign up to set email alerts
|

An efficient synthesis of benzodiazepinyl phosphonates as clostripain inhibitors via FeCl3 catalyzed four-component reaction

Abstract: A novel one-pot route for the synthesis of benzodiazepinyl phosphonates (BDPs) has been achieved. FeCl(3) efficiently catalyzed four-component condensation of diamines, acetone and phosphites in the presence of molecular sieves to furnish BDPs as novel chemical entities with good yield. The synthesized BDPs have shown significant protease inhibition activity against clostripain, a disease model for gas gangrene, suggesting that these novel chemical entities could be further explored as cysteine protease inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Moreover, several structures based on an α‐amino phosphonic acid moiety, such as dufulin, show pesticide activity. Other interesting derivatives are cyclic α‐amino phosphonates, which present a broad biological spectrum such as antibiotics or proteinase inhibitors …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several structures based on an α‐amino phosphonic acid moiety, such as dufulin, show pesticide activity. Other interesting derivatives are cyclic α‐amino phosphonates, which present a broad biological spectrum such as antibiotics or proteinase inhibitors …”
Section: Figurementioning
confidence: 99%
“…[2] Moreover, severals tructures based on an a-amino phosphonic acid moiety,s uch as dufulin, [3] show pesticide activity.O ther interesting derivativesa re cyclic a-aminophosphonates, which presentabroad biological spectrum such as antibiotics [4] or proteinase inhibitors. [5] Severalm ethods for the synthesis of a-aminop hosphonic acid derivatives have been reported. [6] However,o nly scarce asymmetrica pproaches to cyclic a-amino phosphonica cids are available.…”
mentioning
confidence: 99%
“…The second method comprises a one-pot four-component reaction of diamines 130 , ketones 131 and phosphites 132 in the presence of FeCl 3 as a catalyst to give benzodiazepinylphosphonates 133 and 134 and has been reported by Bhattacharya et al ( Scheme 28 ) [ 54 ]. The authors observed that the presence of molecular sieves (4 Å) had a beneficial effect on the yield of the reaction due to trapping of water resulting from the imine formation reaction.…”
Section: Reviewmentioning
confidence: 99%
“…In 2011, Bhattacharya et al published the FeCl 3 catalysed one-pot, four-component condensation of diamines 13, acetone (14a) and phosphinate (15) in the presence of MS 4A, providing benzodiazepinyl phosphonates (BDPs) 16 with high yield (Scheme 4). 11 The water generated during the initial imine formation can decompose or deactivate the catalyst, which can be avoided by the use of MS 4A. When preactivated MS 4A was applied at room temperature, the reaction was complete within 1 hour and gave the desired products with 42-66% yield.…”
Section: Scheme 3 Reactions Between -Keto Esters 10 and Acetylenes 11mentioning
confidence: 99%